Methods for performing error correction and a system thereof. - Mokhtar, Makhfudzah; Wan Adnan, Wan Azizun; Lee, Siao Ping (2011)
The present invention includes methods and a system to perform error correction for QKD information reconciliation. The invention includes a quadruple error correction capability to facilitate unconditional secure QKD, for communication with high security requirements.